2020
DOI: 10.11591/ijere.v9i2.20476
|View full text |Cite
|
Sign up to set email alerts
|

Correlating spiritual and emotional intelligence with academic performance among Pakistani students

Abstract: Continuous learning works like a blood for organization and individuals to proceed and succeed. Underdeveloped countries need to address their academic issues. Academic prosperity is linked to economy and technology disruptions so it’s an important element to bring underdeveloped countries up to the mark to thrive and survive in this technical era. Academic prosperity depends upon student's enthusiastic attitude and their emotional and spiritual intelligences. This study was conducted in learning organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
1
7
0
6
Order By: Relevance
“…In addition to the influence of knowledge, age, and family factors, gender also affects the attitudes and behavior of each individual (Mardiani et al, 2021;Mengel et al, 2018;Syahrial et al, 2019). With these gender differences, it can affect academic achievement positively but not consistently (Indrahadi & Wardana, 2020;Turi et al, 2020). For this reason, so that academic achievement can develop consistently, there must be a willingness and commensurate effort from each individual.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the influence of knowledge, age, and family factors, gender also affects the attitudes and behavior of each individual (Mardiani et al, 2021;Mengel et al, 2018;Syahrial et al, 2019). With these gender differences, it can affect academic achievement positively but not consistently (Indrahadi & Wardana, 2020;Turi et al, 2020). For this reason, so that academic achievement can develop consistently, there must be a willingness and commensurate effort from each individual.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also confirmed the second hypothesis that there is a relationship between spiritual intelligence and students' academic conscience. Turi et al (2020) and Kızıldağ et al (2017). Fatin et al…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive and significant relationship between all four dimensions of spiritual intelligence and students' academic performance. Turi, Rani, Abidin, Mahmud, and Al Adresi (2020) concluded that the relationship between spiritual and emotional intelligence and academic performance among students is significant and positive. Özhan and Kocadere (2020) concluded that academic engagement in an online learning environment has a very significant effect on motivation.…”
Section: Relationship Between Spiritual Intelligence and Academic Eng...mentioning
confidence: 99%
“…Referring to the results of theoretical and empirical studies, it was evident that the learning organization has a significant positive impact on an organization's ability and performance. Turi, et al [48] revealed the relationship between learning organizations and emotional intelligence and spiritual intelligence in improving academic performance, productivity, efficiency, and effectiveness. This study is in line with Edmonson in Salas, et al [49], which states that "learning teams directly promote performance and indirectly promote organizational performance."…”
Section: Lecturers' and Employees' Perceptionsmentioning
confidence: 99%